If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 8 = 8x + -29 Reorder the terms: 8 + 11x = 8x + -29 Reorder the terms: 8 + 11x = -29 + 8x Solving 8 + 11x = -29 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 8 + 11x + -8x = -29 + 8x + -8x Combine like terms: 11x + -8x = 3x 8 + 3x = -29 + 8x + -8x Combine like terms: 8x + -8x = 0 8 + 3x = -29 + 0 8 + 3x = -29 Add '-8' to each side of the equation. 8 + -8 + 3x = -29 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = -29 + -8 3x = -29 + -8 Combine like terms: -29 + -8 = -37 3x = -37 Divide each side by '3'. x = -12.33333333 Simplifying x = -12.33333333
| 59-4x=32x+15 | | -28X-6X=12-10X | | 14-9x=199-44x | | 3+7x=27+1x | | 11X+22=4X+113 | | 2.16x^2-5.40x-3.24=0 | | 60-x=19 | | x-6/10+x-4/15=x+2/6 | | 12*(x-2)+6*(5-x)=4x-6 | | x^4+12x^3+36x^2-64=0 | | 5w^8-45w^7-50w^6=0 | | 3x-4(1-3x)=2x-(x-1) | | 3(x+2)/5=6 | | 4-2(3-2x)=5 | | X+x+x=16 | | 3-5(2x+1)=2x | | 3y^2-9y-84=0 | | 7(2x-1)=-35 | | A(b-2)=c(b+3) | | 6(x+5)=-12 | | 5(x-2)-3(x+1)=0 | | 6x-3=6x+2 | | 100-10x=40 | | x^2-10xy-24y^2=0 | | 9(x-5)-5(x-2)+2x= | | 2y=8-(y-2) | | 5(x+1)=12-x | | 18x+72=21 | | N+7=4 | | 9x+7x=69+x | | 5x-1=3x+115 | | 2x+38=4x+12 |